1. 3x + 2y = 11
y = –4x + 8
3x + 2(-4x + 8) = 11
3x – 8x + 16 = 11
3x - 8x + (16 - 16) = 11 - 16
===> -5x = -5
===> x = 1
y = -4(1) + 8
y = -4 + 8
y = 4
so the solution is (1,4) is that right?
Am not sure on equation #2
2. x – 3y = 10
–2x – 4y = 10
In the interest of using a few fractions as possible solve the top equation for x:
x = 3y + 10
and insert this into the bottom equation:
-2(3y + 10) - 4y = 10
-6y - 20 - 4y = 10
-10y - 20 = 10
-10y = 30
y = -3
Thus
x = 3(-3) + 10 = -9 + 10 = 1
So your solution is
(x, y) = (1, -3)
-Dan